A novel methodology for fault size estimation of ball bearings using stator current signal. (February 2021) - Wang, Chen; Wang, Min; Yang, Bin; Song, Kaiyu; Zhang, Yiling; Liu, Liming
Highlights: A computational model of experimental motor is developed to extract fault-excited harmonic components. A new indicator is proposed for evaluating the severity of bearing fault-excited harmonic distortion. There is a fixed functional relation between fault sizes and FHD. The specific fault size can be estimated based on the proposed methodology that uses stator current signal. Abstract: Bearing fault diagnosis that utilizes motor current has shown great potential for industrial application. For estimating fault sizes, this paper develop an electromechanical-magnetic coupling computational model of induction motor (IM) based on modified winding function approach (MWFA) in order to extract the fault-excited harmonic components and amplitudes in stator current. A new evaluating indicator FHD (Fault-excited Harmonic Distortion) is then proposed to describe the specific relation between fault sizes and severity of fault-excited harmonic distortion. The statistical results show that there is a fixed functional relation curve between FHD and fault sizes in different IM. Finally, an experimental IM with a known size built-in faulted bearing is investigated. The 1 mm artificial damage on outer raceway is recognized by calculating FHD (0.5636 in average) value and comparing with the simulated relation curve. The results validate the accuracy and robustness of the proposed approach in fault size estimation.